2021
DOI: 10.1080/17549507.2021.1975817
|View full text |Cite
|
Sign up to set email alerts
|

Effect of effortful swallow on pharyngeal pressures during swallowing in adults with dysphagia: A pharyngeal high-resolution manometry study

Abstract: Purpose: Evidence base to support use of the effortful swallow in clinical populations with dysphagia is currently lacking. This study aims to quantify the effects of effortful swallowing on pharyngeal swallowing biomechanics in adults with dysphagia using pharyngeal high-resolution manometry (PHRM).Method: ManoScan HRM equipment with a 4.2 mm pressure catheter was used.Participants completed duplicate 10ml baseline and 10ml effortful liquid (IDDSI Level 0) swallows in randomized order. PHRM data were analysed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 32 publications
(70 reference statements)
0
9
0
Order By: Relevance
“…Twelve of these 15 studies evaluated healthy participants (total n = 299) using pressure-based outcome measures (pressure peak or pressure duration) ( n = 11 studies) [ 14 , 15 , 26 31 , 34 , 35 , 37 ] or magnetic resonance imaging ( n = 1 study) [ 32 ]. Three studies evaluated immediate effects in patients with dysphagia [ 25 , 33 , 36 ]. Of these, one study investigated the effortful swallow in three patients with HNC [ 25 ] using low-resolution videomanometry.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Twelve of these 15 studies evaluated healthy participants (total n = 299) using pressure-based outcome measures (pressure peak or pressure duration) ( n = 11 studies) [ 14 , 15 , 26 31 , 34 , 35 , 37 ] or magnetic resonance imaging ( n = 1 study) [ 32 ]. Three studies evaluated immediate effects in patients with dysphagia [ 25 , 33 , 36 ]. Of these, one study investigated the effortful swallow in three patients with HNC [ 25 ] using low-resolution videomanometry.…”
Section: Resultsmentioning
confidence: 99%
“…All three of these patients presented with BOT-PPW contact pressures that were lower during normal control swallows than what had been reported for healthy controls. The second clinical study evaluated 15 patients with mixed etiology dysphagia using high-resolution manometry (HRM) ([ 36 ]. In both of these clinical studies, attempts were made to confirm that patients presented with instrumentally confirmed impairment of BOT-PPW approximation during control swallows either by comparison to published values in healthy controls [ 25 ] or comparison to median values within the patient group studied [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Effortful swallow, special maneuvers, volume, and viscosity have been shown to impact changes in PhCI values in adults 7,14,18‐20 . Due to practical and logistic issues, we did not evaluate these in young children.…”
Section: Discussionmentioning
confidence: 99%
“…Current recommendations on P‐HRM‐I assessments of oro‐pharyngeal swallowing include guidance on deriving eight physiological measures that define pharyngeal contractile vigor as well as UES pressure relaxation and opening 8 . These parameters have already been helpful for characterizing the physiological and potential rehabilitative effects of swallowing exercise, 9,10 sensory stimulation, 11 and novel surgical interventions 12,13 . These measurements can complement routine clinical and instrumental swallowing assessments by adding understanding of the pathophysiology of dysphagia that may help guide patient management.…”
Section: Introductionmentioning
confidence: 99%